(untitled) - Bolman, Lee G. (San Francisco, 2003)
In this third edition of their best-selling classic, authors Lee Bolman and Terrence Deal explain the powerful tool of "reframing." The authors have distilled the organizational literature into a comprehensive approach for looking at situations from more than one angle.
Keywords: Management,Organizational behavior,Leadership